Pengaruh Strategi Bauran Pemasaran terhadap Peningkatan Loyalitas Nasabah pada BPRS Bhakti Sumekar Kantor Cabang Pamekasan - Yenny Kuratul Aini; Wadhan Wadhan (Institut Agama Islam Negeri Madura, 2016)
The Institute of Syariah banking continues to grow in Indonesia from urban to rural areas, particularly BPRS Bhakti Sumekar on branch office of Pamekasan in the activities implementation based on syariah principles, as well as in terms of marketing. BPRS Bhakti Sumekar on branch office of Pamekasan is one financial institution that has increased exponentially customers annually. The increase in the number of clients allegedly because of the trust and customer satisfaction so as to form loyalty. One of the advantages possessed by the BPRS Bhakti Sumekar on branch office of Pamekasan in terms of products, namely savings Barokah with the principle wadi'ah (surrogate) and sharia-based providing easiness for customers with initial deposit and the minimum balance of Rp. 10.000 as well as free of administrative costs that are not owned by other Syariah financial institutions in Pamekasan. Based on this background, researchers interested in conducting research with the title